2012
DOI: 10.1371/journal.pone.0036565
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Wnt Co-Receptor LRP6 Promotes Hepatocarcinogenesis and Enhances Cell Invasion

Abstract: BackgroundActivation of the Wnt/β-catenin signaling pathway plays a crucial role in hepatocellular carcinoma (HCC). Low-density lipoprotein (LDL) receptor-related protein-6 (LRP6) is one of the co-receptors of the Wnt/β-catenin pathway and forms a signaling complex with Wnt ligand and Frizzled receptor to activate downstream signaling. However, the role of LRP6 in hepatocarcinogenesis is unclear. In this study, we examined its expression and roles in human HCC.Methodology/Principal FindingsUsing real-time quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…6). LRP6 has been shown to function as an oncogene by promoting cell growth, invasion and migration, and is expected to be a target for cancer therapy (40)(41)(42)(43)(44)(45). Notably, there is evidence that ERK1/2 in the RAS/MAPK pathway could facilitate WNT/β-catenin signaling via LRP6 phosphorylation on serine-1490 (S1490) and threonine-1572 (T1572) at both mature (transmenbrane LRP6) and immature state during its Golgi network-based maturation process (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…6). LRP6 has been shown to function as an oncogene by promoting cell growth, invasion and migration, and is expected to be a target for cancer therapy (40)(41)(42)(43)(44)(45). Notably, there is evidence that ERK1/2 in the RAS/MAPK pathway could facilitate WNT/β-catenin signaling via LRP6 phosphorylation on serine-1490 (S1490) and threonine-1572 (T1572) at both mature (transmenbrane LRP6) and immature state during its Golgi network-based maturation process (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…As an essential Wnt-co-receptor, LRP6 is overexpressed in several types of cancer [Lindvall et al, 2009; Liu et al, 2010; Yang et al, 2011; Liu et al, 2012b; Tung et al, 2012], and represents a promising therapeutic target for the development of novel anticancer drugs [King et al, 2012]. It has been demonstrated that LRP6 deficiency in human TNBC MDA-MB-231 cells resulted in significantly decreases of Wnt/β-catenin signaling, cell proliferation, and tumor growth in vivo [Liu et al, 2010], and that blocking Wnt/β-catenin signaling by N-myc downstream regulated gene-1 (NDRG1), a tumor metastasis suppressor which interacts with LRP6 and represses Wnt/β-catenin signaling, led to drastic suppression of metastatic phenotypes of mammary tumor cells in vitro and in vivo [Liu et al, 2012b].…”
Section: Discussionmentioning
confidence: 99%
“…The LRP6 R611C mutation promoted PDGF stimulated VSMC proliferation and [86], dedifferentiation and neointimal thickening via the non-canonical Wnt signaling pathway [85]. Recent studies have shown that overexpression of LRP6 enhances cell proliferation and induces tumorigenesis in fibrosarcoma [102], hepatocellular carcinoma [103], and breast [104,105] and colorectal [106] cancer. In conclusion, aberrant activation of LRP6 gene plays a major role in pathophysiology of both diseases and may be as one of the genetic links between CVD and cancer.…”
Section: Shared Molecular and Genetic Pathways In Cvd And Cancermentioning
confidence: 99%